La técnica de elección de W. Morgenthaler - Jímenez Gómez, Fernando (1991)
The paper attempts to analyse the answers of adolescents and adults through the Morgenthaler technique in order to obtain some differenciative data regarding their characteristics of personality.Two samples were selected: 526 adolescents and adults, of both sexes. The average age of the adolescents was 15 years 6 months, and the mean age of the adult group was 37 years 2 months. The Morgenthaler tecnique was used after all the subjects were administered the Rorschach Test and "Láminas Proyectivas".Results show that although there are cards which are accepted or rejected by the same groups of subjects, there are, however, some other cards whose acceptance or rejection is due to the different characteristics of personality of the groups selected.